ANALISIS DISPARITAS PUTUSAN DALAM PERKARA TINDAK PIDANA PENYEBARAN BERITA BOHONG DAN TINDAK PIDANA PENCUCIAN UANG (Studi Kasus Putusan No. 1240/Pid.Sus/2022/ PN Tng dan Putusan No. 576/Pid.Sus/2022/PN Blb) - Sihombing, Santa Sentia; Rahmadan, Davit; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Criminal disparity is the application of unequal punishments to the samecrime or crimes whose nature and danger can be compared. This researchfocuses on the verdict on the crime of spreading false news and money launderingwith the defendants Indra Kenz and Doni Salmanan. Where the problem thatoccurs is disparity in punishment, namely in the application of different principaland additional penalties so that it is seen as not fulfilling a sense of justice.The aim of this research is to analyze the disparity in decisions in thesecases and how the regulations or policies of judges as law enforcers are related todisparities in judges' decisions. This research uses a normative juridical methodwhich is descriptive analysis. This research uses legal sources consisting ofjudges' decisions in cases will be analyzed, related legislation, books andscientific journals. All data collected will be compiled and analyzed using theoryor expert opinion.The results of the research and discussion carried out present the resultsof the analysis of disparities in judge's decisions in cases of criminal acts ofmoney laundering and spreading false news committed by defendants Indra Kenzand Doni Salmanan, as well as explaining regulations and policies to minimizedisparities in decisions. Criminal disparity is a decision by a panel of judgesregarding similar criminal acts. The differences in judge's considerations and theexistence of unproven charges have led to disparities in punishment (main andadditional penalties) in criminal cases of spreading fake news and moneylaundering Decision No.1240/Pid.Sus/2022/PN Tng and Decision No.576/Pid.Sus/2022/PN Blb. The cause of the disparity is the lack of legal reasoning amongjudges who tend to accept whatever is offered by the public prosecutor.Regulations and policies related to disparities are still developing. In an effort tobuild accountable law enforcement, the quality of moral and juridicalaccountability is required from judges.Keywords: Disparity, Judge's Decision, Spread of Fake News, MoneyLaundering.